Catalogue 2.0 : future of the library catalogue - Chambers, Sally (London : Facet, 2013)
New digital technologies, the Internet, and user expectations have changed the role of the catalogue in libraries considerably in recent years. This timely book takes into account developments that influence catalogue potential and patrons needs, such as competition from popular Web sites like Facebook, Twitter, and Wikipedia. Here, key leaders in the field like OCLC. This book also explores concepts like: -What do your users want? Designing the catalogue for the end user ; Making search work for the library user search ; Beyond the catalogue: expanding the scope of search ; From catalogue to digital library : rethinking metadata management in the web age ; The mobile library catalogue -The facets of FRBR: FRBRising your catalogue ; Enabling your catalogue for the semantic web Librarians and information professionals will find practical guidance on customizing their catalogues to keep them up to date with the latest trends in technology in this authoritative manual.
Includes bibliographical references and index.
oif 17/09/14
Loan
Keywords: Online library catalogs; Web 2.0.; Semantic Web